Parenting Style, Effect, Identity in Career Choice-Collectivisme Theory - Fika Dwi Mulia; Afdal Afdal; Rezki Hariko; Finda Yolanda (Jurnal Counseling Care, 2025)
It’s influence on adolescent career development in a collectivist context, but only a few studies have succeeded in integrating these variables, namely parenting style, influence, identity. This article aims to analyze relevant research to determine parenting style, influence, identity in career choice-collectivism theory. This research is descriptive research with a systematic literature review (SLR) method. Literature data was obtained from several pages such as Google Scholar, Sinta Ristekbrin, and Garuda Ristekbrin. To review the data literature, the main keywords used are "career choice" "career" "Parenting Pattern" "Identity". From the literature that has been reviewed, it is known that parenting style and self-identity help children with career aspects. Overall research shows that the parenting style of parents or teachers at school greatly influences children's conservation choices. Authoritarian parenting styles influence children's thinking styles. It has been proven by several pieces of literature from research results that show that the most common parenting style used by parents is authoritarian parenting. Meanwhile, making career decisions requires broader complex factors, including information about career, talents, self-concept, values and personal interests. This conclusion is supported by differences in research results. Career decisions are usually influenced by broader issues, even when a person's thinking and behavior is influenced by a parent's authoritarian parenting approach. This is because not everyone who was raised in an authoritarian environment is unable to overcome the negative impacts of this parenting style, some people who were raised in an authoritarian environment may show a high level of obedience but still have good career decision-making skills Keywords: Parenting Style, Influence, Identity, Career Choices